African literature and criticism discourse - (:unkn) unknown (My University, 2005)
This study examines the emergence of Subsaharian Francophone African criticism. In the beginning we try to proove that traditionnal african society have also a kind of criticism which applyed on the tales, legends and myths. In colonisation's years appears a criticism which is only claims his support about colonial system. With the Négritude movement, criticism became one occasion to show African civilisation value. Critics think that literature and novelists must be against colonisation. In seventies some critics like M. Kane, A. Koné and others established that the sources of African novel can be found in the African story-telling tradition. After, we try to show the another criticism discours : the influence of new european criticism with S. Anozié, question about the language used by writers and the criticism of female writers. We also examine how magazine talk about African literature.
Keywords: African Research